Characteristics of Postoperative Patients with Breast Cancer Aged 65 Years and Older - Yoshiteru Akezaki; Eiji Nakata; Masato Kikuuchi; Ritsuko Tominaga; Hideaki Kurokawa; Masaki Okamoto; Toshifumi Ozaki; Kenjiro Aogi; Shozo Ohsumi; Shinsuke Sugihara (Current Oncology, 2023)
Objective: This study aimed to compare postoperative patients with breast cancer aged ≥65 years with those aged <65 years and clarify the characteristics of postoperative patients with breast cancer aged ≥65. Methods: In total, 376 patients in whom we were able to evaluate survey items one month after surgery were included in the study. Comorbidity, including diabetes mellitus and hypertension, shoulder range of motion (ROM), upper-limb function, and psychological problems, was evaluated. Results: Hypertension and diabetes mellitus were significantly higher in patients aged ≥65 years (the elderly group) than in those aged <65 years (the non-elderly group) (p < 0.05). Preoperative shoulder flexion ROM was significantly restricted in the elderly group compared with the non-elderly group (p < 0.05). Preoperative shoulder abduction ROM was significantly restricted in the elderly group compared with the non-elderly group (p < 0.05). At one month after surgery, upper-limb function was more impaired in the non-elderly group than in the elderly group (p < 0.05). In both groups, both ROM and upper-limb function were significantly impaired one month after surgery compared with before surgery (p < 0.05). Conclusions: Postoperative patients with breast cancer aged ≥65 years should be careful about risk management and intervention during rehabilitation. Preoperative evaluation of shoulder ROM should be performed because patients aged ≥65 years have limited ROM before surgery.